New integral inequalities for (s,m)- and ( α ,m)-preinvex functions - Meftah, Badreddine; Aouissi, Nassima (Revista MATUA, 2018)
In this note, we give some estimate of the left hand side of generalized quadrature formula of Gauss-Jacobi in the cases where $f$ and $\left|f\right| ^{λ }$ for $λ >1$, are $\left( s,m\right) $- and $ \left( α ,m\right) $-preinvex functions.